Efficacy and safety of cannabidiol in a single-center pediatric drug-resistant epilepsy cohort: a retrospective study - Butera, Ambra; Spoto, Giulia; Ceraolo, Graziana; Grella, Maria; Giunta, Ivana; Albertini, Maria Ludovica; Consoli, Carla; Sferro, Caterina; Spanò, Maria; Di Rosa, Gabriella; Nicotera, Antonio Gennaro (Frontiers in Neurology, 2025)
BackgroundPharmacoresistance to conventional antiseizure medications has been described in approximately 30% of the pediatric epileptic patients, making pharmacological management particularly challenging for physicians. Currently, cannabidiol (CBD) is approved as an adjunctive therapy in combination with clobazam for Dravet Syndrome (DS), Lennox–Gastaut Syndrome (LGS), and as adjunctive treatment for Tuberous Sclerosis Complex (TSC). Studies on drug-resistant epilepsy (DRE) suggested that CBD antiepileptic properties may benefit a wider range of pharmacoresistant epilepsy syndromes.ObjectiveOur observational, retrospective, monocentric study aimed to evaluate the effect and safety of CBD in a real-world pediatric cohort with DRE.MethodsWe recruited 15 pediatric patients (7 females, 8 males; mean age: 12.33 ± 4.37 years) affected by pharmacoresistant epilepsy treated with CBD as adjunctive therapy. Inclusion criteria required a diagnosis of DRE, initiation of CBD treatment before 18 years of age, and at least 6 months period of follow-up after CBD initiation. Clinical, demographic, and instrumental data were retrospectively extracted from the medical records and caregivers’ reports. Based on seizure reduction, patients were stratified into “responders” (>50%), “partial responders” (30–50%), and “non-responders” (<30%) groups.ResultsCBD was used as an add-on therapy in 8/15 patients on-label (for DS, LGS, and TSC) and in 7/15 off-label. The maximum dose of CBD administered was 21 mg/kg/day, with an average dose of 16.5 mg/kg/day. 11/15 patients showed a reduction in seizure frequency: 7 were responders (2/7 seizure-free) and 5 were partial responders. Additionally, 11/15 patients showed improved social and environmental participation, as assessed using the Clinical Global Impression scale. Interestingly, brain magnetic resonance imaging revealed structural abnormalities in 5/15 patients, with 6/15 showing malformations of cortical development (4/6 responders, including 1 seizure-free).ConclusionCBD demonstrated a good safety and tolerability profile and appeared to be a promising therapeutic option for the management of DRE. It offers a valuable alternative for seizure control and has a positive impact on social interaction, with overall improvement in the quality of life for patients and their caregivers.